Politics and Beatitude - Gregory, Eric (Studies in Christian ethics, 2017)
The limits and secularity of political life have been signature themes of modern Augustinianism, often couched in non-theological language of realism and the role of religion in public life. In dialogue with Gilbert Meilaender, this article inverts and theologizes that interest by asking how Augustinian pilgrims might characterize the positive relation of political history to saving history and the ways in which political action in time might teach us something about the nature of salvation that comes to us from beyond history. This relation of continuity and discontinuity eludes dogmatic formulation, but the goal of the present article is to see where a shared Augustinianism and a shared commitment to aspects of the liberal political tradition might find illuminating disagreement.